Fibroblast contributes for osteoblastic phenotype in a MAPK-ERK and sonic hedgehog signaling-independent manner - da Costa Fernandes, Celio J. [UNESP]; do Nascimento, Augusto Santana [UNESP]; da Silva, Rodrigo A. [UNESP]; Zambuzzi, Willian F. [UNESP] (Springer Nature, 2017)
We hypothesized that a crosstalk between osteoblast and fibroblast (FB) exists, which contributes to bone as a dynamic tissue. Cell-free supernatants were harvested from fibroblast cultures and later subject pre-osteoblasts to investigate there capacity to modulate cell viability and differentiation mechanisms, reporting the possible involvement of Shh signaling as a paracrine mechanism. By exploring immunoblotting technology, we have shown that FB-released factors interfere with osteoblast metabolism by up-regulating the phosphorylation of FAK and Rac-1 proteins at the early stage and later contribute to osteoblast differentiation by up-modulating alkaline phosphatase (ALP) and in vitro mineralization. We also found that Shh signaling was not required during osteoblastic differentiation promoted by the FB-released factors as well as MAPK-ERK phosphorylation, while pre-osteoblast cultures subjected to osteogenic medium (O.M.) require downstream transducers of Shh, such as Patched and Gli-1, and MAPK-ERK. Altogether, our results indicate for the first time a possible mechanism involved in the crosstalk between fibroblasts and osteoblasts, as it was possible to observe trophic factors released by fibroblasts interfering decisively in osteoblast metabolism in a Shh-independent manner. This study collaborates the body of work that indicates paracrine signaling molecules participate in the crosstalk among bone-resident cells and explains, at least partially, the biological mechanisms responsible for bone tissue dynamism, opening new avenues to understand etiologies of bone diseases.
Keywords: Bone; Cell signaling; Crosstalk; Fibroblast; Osteoblast